Overview of patents of Federal Universities through patent quality metrics and impact on innovation from the database of the European Patent Office - PATSTAT EPO 2010-2020 - Leonidio, Ueliton da Costa (2023)
This study aims to provide a scenario and indicate the quality of patent registration in Brazilian federal universities from the database of the European Patent Office - EPO and PATSTAT between the years 2010 and 2020, considering the deposits, grants and other relevant data for research. The data were obtained in SQL language and were treated through data integration, supported by MS Power BI software, bringing contributions to the research profile in this international bank, such as the number of patents, research area profile, number of inventors, offices that received patent deposits, patent citations by family, geographic location, profile through patent classes, to understand the innovative process and pure invention, besides helping to improve processes, promote better partnerships, investments in more vital areas and to know the know-how of Universities in specific research areas. Finally, we note the 461-fold increase in the number of filings on this international base since 2015, indicating the maturity of Brazilian university patenting, and the concentration of universities in the Northeast, Southeast, and South. Based on the International Patent Classification (IPC), the most prominent areas are health, medical or veterinary clinics and hygiene (A61), representing 41.48% of the total number of patents, the area of microorganisms or enzymes, their compositions; propagation, conservation or maintenance of microorganisms, genetic or mutational engineering, culture media (C12), representing 12.29% of the total number of patents, the area of Food and food products (A23), microorganisms or enzymes; their compositions; propagation, preservation or maintenance of microorganisms represents 11.69% of patents, and area of organic chemistry (C07) represents 9.12% of patents and the area of investigation or analysis of materials by determining their chemical or physical properties (G01) which represents 6.18% of the total number of patents. The most prominent universities are UFPA, UFMG, UFPE, UFRGS, UFCE, UFPR, UFPEL, UFRN, UTFPR.